Strategi Promosi Dinas Pariwisata Kabupaten Semarang untuk Meningkatkan Wisatawan Candi Gedong Songo - Setiawan, Marcelus Bima; Vanel, Zon (Jurnal Pustaka Komunikasi, 2023)
Indonesia is a country that has great tourism potential. The emergence of the covid-19 pandemic has had a negative impact on the potential of Indonesian tourism. The pandemic has made the tourism sector in various regions slumped, one of which is in Semarang Regency, Central Java Province. Gedong Songo Temple is a leading tourist attraction in Semarang Regency experiencing a decrease in tourist visits due to the pandemic. So tourist visits have not increased significantly. Based on these problems, it is interesting to examine how the promotion strategy of the Semarang Regency Tourism Office increases tourist visits at Gedong Songo Temple.. This research uses the case study research method. This research is included in the type of qualitative descriptive research. The data collection techniques used are interviews, observations, and documentation. The results showed that the Semarang Regency Tourism Office carried out five promotional mix strategies, namely advertising, personal sales, sales promotion, public relations, and direct sales to increase tourist visits at Gedong Songo Temple. In general, the promotion strategy of the Semarang Regency Tourism Office is good enough to help increase tourist visits at Gedong Songo Temple.